Culture-independent quantification of pathogenic bacteria in spices and herbs using real-time polymerase chain reaction. (January 2018) - Minarovičová, Jana; Cabicarová, Tereza; Kaclíková, Eva; Mader, Anneluise; Lopašovská, Janka; Siekel, Peter; Kuchta, Tomáš
Abstract: A culture-independent method was developed for quantification of pathogenic bacteria in spices and herbs. The method is based on DNA extraction using cetyltrimethylammonium bromide (CTAB) and on real-time polymerase chain reaction (PCR). When evaluated with spices (black pepper, paprika) and herbs (oregano, parsley) artificially contaminated with Staphylococcus aureus, Salmonella enterica or Escherichia coli, the method demonstrated quantitative response with linear calibration lines and quantification limits of 10 2 –10 4 CFU/g. The developed method is suitable for rapid microbiological analysis of spices and herbs, taking 8–9 h. Highlights: Culture-independent quantitative microbiological analysis within 8–9 h. DNA extraction using cetyltrimethylammonium bromide (CTAB) followed by real-time PCR. Quantification of Staphylococcus aureus, Salmonella enterica and Escherichia coli . In spices (black pepper, paprika) and herbs (oregano, parsley). Linear response, quantification limits of 10 2 –10 4 CFU/g.